“INCLUSION RIDER” E A FUNÇÃO SOCIAL DO CONTRATO DE ENTRETENIMENTO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Receiving the award for best actress at the 2018 Oscar, Frances McDormand gained prominence by using the term: Inclusion Rider, which is a kind of "equity clause", which provides, at the signing of a contract, that the individual can specify his particular desires, promoting the equality of professional conditions. The study deepens the concept of Inclusion Rider and the dimension of social function in entertainment contracts, broadening the perspectives of inclusion, citizenship and democratization of access in the field of cultural productions and minority participation. Under the hypothetical-deductive method the research focused on the concept of Inclusion Rider, idealized by Stacy Smith in a talk of the series TED Talks in 2016, that has aroused the interest in its particularities and practical application.